Covid-19 skepticism and public health norms during refugee assistance: does skepticism always lead to poor safety protocol adherence? - Stephanie J. Nawyn; Ezgi Karaoğlu; Natalie Qaji; Natalynn Qaji (BMC Public Health, 2024)
Abstract Background Skepticism about COVID-19’s existence or severity has spread as fast as the disease itself, and in some populations has been shown to undermine protective public health behaviors that can mitigate infection. For populations that are especially vulnerable to COVID spread and severity, such as refugees, COVID skepticism is particularly problematic. Methods We examine data collected from observations of humanitarian services provided to refugees in Lebanon, Türkiye, and Jordan to determine if skepticism is related to adherence to specific health-protective protocols (masking, social distancing, and hand sanitizing), and whether the effects of COVID skepticism are mediated by particular populations of refugees or the country in which those refugees receive assistance. Results We found that community skepticism (the frequency of COVID skepticism expressed by others within a service location) is associated with lower adherence to certain protocols and not others. We also found that with certain protocols, the country in which refugees receive services mediates the relationship between community skepticism and protocol adherence, but for other protocols the relationship between skepticism and adherence is independent of either country in which refugees reside or the refugee population being served. Conclusions The existence of skepticism about COVID-19 does not always lead to an unwillingness to take protective measures to avoid infection. The mechanisms underlying the relationship between skepticism and adherence to health-protective protocols vary based on the type of protocol in question. In order to increase protocol adherence, the specific variables predicting adherence to different protocols need to be assessed in order to increase adherence and improve public health during humanitarian services.